2014
DOI: 10.1016/j.ultsonch.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of polyphenols from black tea – Conventional and ultrasound assisted extraction

Abstract: Products from plant raw materials gain increasing importance in food-, cosmetics and pharmaceutical industry. By way of contrast, due to lack of detailed physico-chemical fundamentals, existing production processes are economically not optimal designed. This leads to a need for deeper understanding of the processes and furthermore a systematic process and equipment design for the potentially applicable extraction techniques. Using the example of polyphenol extraction from black tea (Kenya), the conventional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 9 publications
3
63
0
1
Order By: Relevance
“…These mechanical and thermal effects cause the degradation of cell walls, release of cell contents, a greater penetration of solvent into plant material, the increment of mass transfer and thus, the increase of polyphenols yield (Deng et al, 2015;Horžic et al, 2012). Particle size of plant material does not significantly affect polyphenols yield, since ultrasound waves induce reduction of the particle size (approximately 5%), damage of the cells and modification of microstructure, which results in the increase of solvent penetration into herbal matrix and in the higher polyphenols release, regardless of the initial size of plant particles (Both et al, 2014;Deng et al, 2015;Jovanović et al, 2017). Regarding the selection of the extraction medium for ultrasound-assisted extraction, alcohol/water mixture was the most suitable solvent for maximum recovery of polyphenols from Jatropha dioica, Eucalyptus camaldulensis, Origanum majorana and Thymus species, whereas pure alcohol or water could not completely extract polyphenols (Chizzola et al, 2008;Fecka and Turek, 2008;Wong Paz et al, 2015).…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanical and thermal effects cause the degradation of cell walls, release of cell contents, a greater penetration of solvent into plant material, the increment of mass transfer and thus, the increase of polyphenols yield (Deng et al, 2015;Horžic et al, 2012). Particle size of plant material does not significantly affect polyphenols yield, since ultrasound waves induce reduction of the particle size (approximately 5%), damage of the cells and modification of microstructure, which results in the increase of solvent penetration into herbal matrix and in the higher polyphenols release, regardless of the initial size of plant particles (Both et al, 2014;Deng et al, 2015;Jovanović et al, 2017). Regarding the selection of the extraction medium for ultrasound-assisted extraction, alcohol/water mixture was the most suitable solvent for maximum recovery of polyphenols from Jatropha dioica, Eucalyptus camaldulensis, Origanum majorana and Thymus species, whereas pure alcohol or water could not completely extract polyphenols (Chizzola et al, 2008;Fecka and Turek, 2008;Wong Paz et al, 2015).…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…These methods are simple, but involve several disadvantages such as low polyphenols yield, long extraction time and large amounts of plant material and solvent (Mustafa and Turner, 2011;Wang and Weller, 2006). In the recent time, the application of novel extraction procedures, such as ultrasound-assisted, microwave-assisted, supercritical fluid, accelerated solvent and pressurized liquid extractions, have been evaluated (Both et al, 2014;Dahmoune et al, 2015;Milošević et al, 2011;Mustafa and Turner, 2011;Oniszczuk and Podgorski, 2015). According to the literature data, these methods provide various benefits which include higher yield of polyphenols, shorter extraction time, ie.…”
Section: Introductionmentioning
confidence: 99%
“…The second objective of this work was to identifying optimal range of UAM extraction conditions namely the ultrasonic intensity (UI), the processing temperature (T) and the processing time (t) and to develop an effective and eco-friendly ultrasound-assisted extraction strategy for extraction of polyphenol compounds from maritime pine sawdust waste, using response surface methodology. In the third part, three concepts were investigated and compared: conventional multi-stage maceration, ultrasound assisted multi-stage maceration and a combination between them [22] in order to highlight the impact of ultrasound. Moreover, a pilot plant reactor of 30 L extraction tank was investigated at lab optimum conditions to prove that the scale up of the process is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have reported that higher extraction yields could be achieved when an UAE method was adopted on many plant products, such as rutin from flower buds of Sophora japonica [7], oil from tobacco (Nicotiana tabacum L.) seeds [8], carvone and limonene from caraway seeds [9], polyphenols from black tea [10], extraction of carotenoids [11], pectins from grape pomace [12], D-pinitol from carob pods [13], and vanillin from vanilla pods [14]. Those studies mainly looked at optimization of other extraction conditions with regards to efficiency and/or yield.…”
Section: Introductionmentioning
confidence: 99%